The Planning and Execution of Surgical Hand Mission Trips in Developing Countries. Issue 4 (June 2015) - Nugent, Ajani G.; Panthaki, Zubin; Thaller, Seth
<x xml:space="preserve">Abstract</x> Abstract An important teaching tool and overall humanitarian good, medical mission trips are a common theme among health care professionals. These trips encompass large potential for education, global health progress, and cultural exposure, but the logistics of planning and execution are just as great and if not given serious consideration can limit success. This article sets out to explain the importance of planning and to provide specifics that are unique to surgical hand mission trips. Establishing trustworthy relationships, adapting to the host nation's limited resources, and preparing the proper surgical procedures for the particular areas' most common surgical needs are all discussed in this article.